Different Associations of Adipokines in Lean and Healthy Adults - Ebert, T.; Roth, I.; Richter, J.; Tönjes, A.; Kralisch, S.; Lossner, U.; Kratzsch, J.; Blüher, M.; Stumvoll, M.; Fasshauer, M. (Hormone and Metabolic Research, 2014)
Regulation of adipokines in lean adults without metabolic disease and without eating disorders has not been comprehensively elucidated. We hypothesized that some of the established associations of these adipocyte-secreted proteins with anthropometric and biochemical measures of glucose homeostasis, lipid metabolism, renal function, as well as inflammation, differ in healthy and low weight adults as compared to overweight/obese patients. Eighty-one subjects with a body mass-index below 22.0 kg/m2 and without malnutrition or eating disorders, as well as fifty overweight/obese patients, were recruited for the study. Serum concentrations of seven adipokines (adiponectin, leptin, adipocyte fatty acid-binding protein [AFABP], chemerin, fibroblast growth factor [FGF]-21, resistin, retinol-binding protein [RBP]-4) were measured by enzyme-linked immunosorbent assays. Lean probands had significantly higher levels of adiponectin and resistin, as well as lower levels of leptin, AFABP, and RBP-4, as compared to overweight/obese subjects. Serum concentrations of adiponectin, leptin, AFABP, chemerin, and resistin were significantly higher in lean women as compared to men (p<0.05). In lean subjects, fasting insulin independently predicted leptin and resistin concentrations. Furthermore, C-reactive protein was independently associated with circulating AFABP and chemerin. Moreover, lean body mass was an independent predictor of leptin, fat mass predicted AFABP levels, whereas RBP-4 was independently correlated to age and triglycerides. In addition, high density lipoprotein cholesterol predicted AFABP. Our results support the notion that several of these adipokines are regulated in a different manner in lean adults as compared to overweight/obese subjects and patients with eating disorders.
Keywords: adipokines; leanness; metabolism